Iron Stress in Crop Plants and Ways to Overcome it - Prasad, Rajendra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2021)
Iron (Fe) stress is encountered by many crops in calcareous soils with pH above 8.0, which are abundant in India. Most of the times Fe stress goes unnoticed however anyway it affects yield. Aerobic rice and upland rice nurseries also exhibit Fe stress. In many cases frequent adequate irrigation solves the problem. In Fe deficient areas adequate organic manures must be applied, while preparing the field. Application of elemental S and S-containing fertilizers also helps in overcoming Fe stress in plants. In case of serious Fe-stress, ferrous sulphate or Fe-EDTA solution can be sprayed, which effectively overcome the Fe stress problem.